2017
DOI: 10.4073/csr.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

The Tools of the Mind curriculum for improving self‐regulation in early childhood: a sytematic review

Abstract: This Campbell systematic review examines the evidence on the effectiveness of the Tools of the Mind curriculum in promoting children?s self‐regulation and academic skills, in order to inform its implementation in schools. The participants included students of all ages, gender, ethnicity, special education status, language‐learning status, and socio‐economic status. The review summarizes findings from 14 records across six studies conducted in the USA. The Tools curriculum significantly improved children?s math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 63 publications
3
18
0
Order By: Relevance
“…Indeed, one of the most important conditions of conducting a distributional analysis is that the interventions produce positive effects or that hidden effects have not been studied before (Jackson and Page, 2013). These results also echo the insignificant findings from previous studies using QTE to evaluate the effects of early interventions on children's noncognitive outcomes (Bitler et al, 2014) and null findings on SE skills from SE curricula (Baron et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Indeed, one of the most important conditions of conducting a distributional analysis is that the interventions produce positive effects or that hidden effects have not been studied before (Jackson and Page, 2013). These results also echo the insignificant findings from previous studies using QTE to evaluate the effects of early interventions on children's noncognitive outcomes (Bitler et al, 2014) and null findings on SE skills from SE curricula (Baron et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…Although all studies discussed above have demonstrated positive impacts on children's SE development, some studies have found that SE curricula interventions do not affect child outcomes. For example, a systematic review including six experimental studies examined the effectiveness of the Tools curriculum, finding that the curriculum only improved math skills and not a range of SE skills (Baron et al, 2017). But it is also possible that null mean impacts are hiding different effects across the distribution of outcomes (Bitler et al, 2015).…”
Section: Curricula Interventions Promoting Socio-emotional Skillsmentioning
confidence: 99%
“… Diamond et al (2019) reported that Tools of the Mind was effective in improving reading and writing skills assessed with standardized achievement tests. Baron et al (2017) concluded from a meta-analysis that there are small positive effects of Tools of the Mind on reading, self-regulation (direct assessments and ratings), and mathematics achievement, but only the effect for mathematics was statistically significant. Similarly, a recent study by Nesbitt and Farran (2021) concluded that aspects of the teacher–child interaction quality seemed to be more promising to improve student performance than the specific activities described in the Tools of the Mind curriculum.…”
Section: Perspectivementioning
confidence: 99%
“…Tools of the Mind. Tools of the Mind (Bodrova & Leong, 2007) is a comprehensive early childhood curriculum built upon the work of Vygotsky with the purpose of promoting young children's self-regulation and academic skills together by focusing on self-regulation and related social-emotional skills in education settings (Baron, Evangelou, Malmberg, & Melendez-Torres, 2017). In Tools of the Mind, early childhood teachers conduct assessment and implement scaffolding to tailor learning activities so that young children build their self-regulatory skills through meaningful play interactions with their peers.…”
Section: Supporting Preschool-age Children With Early Interventionsmentioning
confidence: 99%
“…In Tools of the Mind, early childhood teachers conduct assessment and implement scaffolding to tailor learning activities so that young children build their self-regulatory skills through meaningful play interactions with their peers. The Tools of the Mind curriculum aims to equip young children with cognitive "tools" for learning, such as inhibitory control, working memory, and cognitive flexibility that they can utilize to acquire and maintain academic knowledge and self-regulation (Baron et al, 2017;Diamond, Lee, Senften, Lam, & Abbott, 2019).…”
Section: Supporting Preschool-age Children With Early Interventionsmentioning
confidence: 99%